KECERDASAN INTERPERSONAL PESERTA DIDIK KELAS XI DI SMK NEGERI 6 PADANG - Gustina, Imelda; Sano, Afrizal; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
The fact showing that learners do not have interpersonal intelligence associated with social interaction and communication. The problem in this research is how the interpersonal level students at SMK 6 Padang. This research aimed to describe the social interaction and communication skills of students.This research is a descriptive study that is tried to describe about one of the condition itself. The population in this study was the students of class XI amounting to 169 people, this study used sample of 62 people. The way of sampling is done by using a proportional random sampling, which samples were taken is compare to the number of population in each class. The sources of data in this study is primary data that is class XI. The data of research were processed using techniques percentage. Results of this study said that interpersonal intelligence of class XIÂ students in terms of social interaction at the high category 83.3%. While on the of communication in middle category means that 95.2% of students have not been able to communicate well with other people.